Cura Encantada: Medicina Tradicional e Biomedicina entre os Pankararu do Real Parque em São Paulo - Lopes, Rafael da Cunha Cara [UNIFESP] (2011)
This essay seeks to approach the Pankararu concepts of healing and their relations with Biomedicine. Although Pankararu originate from the region of São Francisco submid, in the State of Pernambuco, after an intense process of migration, many ofthem took up residence in the shantytown of Real Parque, in São Paulo city. This study focuses on the Pankararu of Real Parque. This paper describes parts of the Pankararu cosmology and their traditional ways ofhealing, seeking to understand the integration of these practices with biomedical care in São Paulo city. I describe,then, how this integration occurs, pointing out the conflictsand the processes of "translation" and their redefinition of ritual elements to the urban context. The growing number of ethnic groups living in the metropolis raises questions aboutthe transformation and upgrading of their speech es. This ethnography aims to explainhow this movement takes place and the forms of identity affirmation and political achievements, especially in the health field.